2011
DOI: 10.1021/jf2028279
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Lignin Structure and Cell Wall Reticulation on Maize Cell Wall Degradability

Abstract: In this study, eight maize recombinant inbred lines were selected to assess both the impact of lignin structure and the impact of cell wall reticulation by p-hydroxycinnamic acids on cell wall degradability independently of the main "lignin content" factor. These recombinant lines and their parents were analyzed for in vitro degradability, cell wall residue content, esterified and etherified p-hydroxycinnamic acid content, and lignin content and structure. Lignin structure and esterified p-coumaric acid conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 29 publications
7
72
0
Order By: Relevance
“…It has been reported that xylo-oligomers are strong inhibitors of cellulase and inclusion of β-xylosidase ( Trichoderma ) reduces the inhibitory impact of these end products on cellulose hydrolysis [16]. Furthermore, xylanases ( Thermoascus aurantiacus ) alone have been shown to enhance the bioconversion of both cellulose and hemicellulose [19]. …”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that xylo-oligomers are strong inhibitors of cellulase and inclusion of β-xylosidase ( Trichoderma ) reduces the inhibitory impact of these end products on cellulose hydrolysis [16]. Furthermore, xylanases ( Thermoascus aurantiacus ) alone have been shown to enhance the bioconversion of both cellulose and hemicellulose [19]. …”
Section: Resultsmentioning
confidence: 99%
“…Indeed, aryl ether bonds are known as labile bonds, less resistant to chemical and biological attacks than other lignin inter-unit bonds. However, they may limit bioconversion of polysaccharides because of the barrier effect, as previously observed for maize (Zhang et al, 2011).…”
Section: Lignin Content and Structurementioning
confidence: 88%
“…This structural parameter, in addition to giving an indication of the global lignin content, is likely to influence the cell wall properties and the bioconversion of lignocellulose. Indeed, Zhang et al (2011) discovered a negative correlation between thioacidolysis yield and the enzymatic degradability of maize stems using a commercial cellulolytic cocktail.…”
Section: Lignin Content and Structurementioning
confidence: 99%
“…Ester-and ether-linked p-coumaric acid (CA) and ferulic acid (FA) were determined by mild and severe alkaline hydrolysis, respectively, as described by Zhang et al (2011).…”
Section: Determination Of Ester-and Ether-bound P-hydroxycinnamic Acidsmentioning
confidence: 99%